The Relationship Between Self Stigma and Family Burden of People with Mental Disorders - Regita Siti Chajar; Cucu Rokayah; Santi Puspitasari; Wini Resna (Jurnal Penelitian Perawat Profesional, 2025)
Mental disorders affect not only the patients but also the families who are the primary caregivers. Families often experience a heavy burden, especially due to self-stigma or negative views internalized from society. Self-stigma can worsen the psychological condition of families and increase the burden of caring for people with mental disorders. The purpose of the research is to determine the relationship between self-stigma and the burden on families of people with mental disorders at the Clinic in Bandung City. The research method uses quantitative analytical correlation with a cross-sectional approach. The research population consists of all 1,165 patients with mental disorders, with a sample of 93 people taken using the accidental sampling technique. Data collection used primary data with questionners from Internalized Stigma of Mental Illness Scale (ISMI) and The Burden Assessement Schdeule (BAS). Data analysis used univariate and bivariate analysis. The results of the univariate analysis showed that (49.5%) of the families of people with mental disorders had moderate self-stigma, and (58.1%) had a heavy burden. The results of the statistical test obtained a p-value (0.001) < α 0.05, which means there is a relationship between self-stigma and the burden on the families of people with mental disorders at the Nur Ilahi Mental Health Clinic in Bandung City. The conclusion indicates that self-stigma experienced by families of people with mental disorders is significantly related to their high burden in caring for family members with mental disorders.